SOCIAL MEDIA AND PRESSURE GROUPS POLITICS DURING THE 2011 UPRISINGS IN EGYPT - OBANI, Eberechukwu Faith (Socialscientia: Journal of Social Sciences and Humanities, 2018)
The importance of social media in our society today cannot be over emphasized. It is increasingly shaping developments in almost all aspects of human activities including education, communication, sports, lifestyle and particularly, politics. Individuals and groups have employed the instrumentality of the social media to effect changes in governance and society. This study therefore, examines the roles social media played in providing platform and empowering groups to fight against repressive regime in Egypt. In the light of this, the study therefore is guided by two research questions: (1) Did effective use of social media facilitate the mobilization of pressure groups during the 2011 uprising in Egypt? (2) Did the activities of pressure groups on social media led to changes in Egypt‘s political structure? The study adopts qualitative method of data collection and invariable the qualitative content method of data analysis. The study utilizes the communication theory as its theoretical framework of analysis. It shows that the effective use of social media facilitated pressure groups activities in Egypt during the 2011 uprising. It also demonstrates that the activities of pressure groups on social media led to changes in Egypt’s political structure. The study concludes that social activism, reinforced by social media played crucial roles in bringing political changes in Egypt during the 2011 uprising.